The Impact of Emotions on Divergent Thinking Processes: A Consideration for Inquiry-Oriented Teachers (LEARNing Landscapes, 2011)
Innovation is a cornerstone of the success of our global society and it is required to generate solutions to today’s challenges. Students will benefit from classrooms that encourage creative thought and innovative self-directed projects. Inquiry is an instructional approach that fosters creativity and divergent thinking. This paper elaborates on one aspect of the creative process—the impact of emotions on divergent thinking. Theory and some existing research are reviewed and a plan for a neurocognitive study using electroencephalography is delineated. Current and previous research is taken into account when reflecting on suggestions for fostering learning environments conducive to creativity and building interdisciplinary collaboration.
Keywords: innovation; creative thought; self-directed projects; inquiry; divergent thinking; instructional approach; emotion; neurocognitive; learning environment; interdisciplinary collaboration